Long‐Term and Seasonal Changes of Large Whale Call Frequency in the Southern Indian Ocean. Issue 11 (27th November 2018) - Leroy, Emmanuelle C.; Royer, Jean‐Yves; Bonnel, Julien; Samaran, Flore
Abstract: In the past decades, in the context of a changing ocean submitted to an increasing human activity, a progressive decrease in the frequencies (pitch) of blue whale vocalizations has been observed worldwide. Its causes, of natural or anthropogenic nature, are still unclear. Based on 7 years of continuous acoustic recordings at widespread sites in the southern Indian Ocean, we show that this observation stands for five populations of large whales. The frequency of selected units of vocalizations of fin, Antarctic, and pygmy blue whales has steadily decreased at a rate of a few tenths of hertz per year since 2002. In addition to this interannual frequency decrease, blue whale vocalizations display seasonal frequency shifts. We show that these intra‐annual shifts correlate with seasonal changes in the ambient noise near their call frequency. This ambient noise level, in turn, shows a strong correlation with the seasonal presence of icebergs, which are one of the main sources of oceanic noise in the Southern Hemisphere. Although cause‐and‐effect relationships are difficult to ascertain, wide‐ranging changes in the acoustic environment seem to have a strong impact on the vocal behavior of large baleen whales. Seasonal frequency shifts may be due to short‐term changes in the ambient noise, and the interannual frequency decline to long‐term changes in the acoustic properties of the ocean and/or in postwhaling changes in whale abundances. Plain Language Summary: In the past decades, a progressive decrease in the frequencies of blue whale vocalizations is observed worldwide. Its causes, of natural or anthropogenic nature, are unclear. Based on 7 years of widespread acoustic records in the southern Indian Ocean, we show that the call frequency of five populations of large baleen whales decreases at a constant rate of tenths of hertz per year. We also found that seasonal shifts in the whale call frequency follow seasonal changes in the ambient noise in the same frequency band. Wide‐ranging changes in the acoustic environment have thus a strong impact on the vocal behavior of large whales in the short term, but, paradoxically, not in the long term. Key Points: The call frequency of five populations of whales in the southern Indian Ocean steadily decreases by few tenths of hertz per year since 2010 Seasonal frequency shifts also occur, particularly for the Antarctic blue whale, and correlate with seasonal changes in the ambient noise The interannual frequency decline may reflect growing whale abundances and/or changing acoustic properties of the ocean